Associations of urinary metal levels with serum hormones, spermatozoa apoptosis and sperm DNA damage in a Chinese population. (September 2016) - Wang, Yi-Xin; Sun, Yang; Huang, Zhen; Wang, Peng; Feng, Wei; Li, Jin; Yang, Pan; Wang, Mu; Sun, Li; Chen, Ying-Jun; Liu, Chong; Yue, Jing; et al.
Abstract: Background: Exposure to metals, including essential and nonessential elements, is widespread and may be associated with male reproductive health. Objective: To examine whether environmental exposure to metals contributes to reproductive hormone changes, spermatozoa apoptosis and sperm DNA damage in a Chinese population. Methods: Eighteen metals (aluminum, arsenic, antimony, chromium, cobalt, copper, cadmium, iron, lead, manganese, molybdenum, nickel, selenium, tin, tungsten, thallium, uranium and zinc) were analyzed in two urine samples collected a few hours apart from male partners of couples attending an infertility clinic. Multivariable linear regression models were used to assess the cross-sectional associations of average urinary metal levels with serum hormones ( n = 511), spermatozoa apoptosis measures ( n = 460) and sperm DNA damage parameters ( n = 516). Results: We found significant inverse dose-dependent trends of urinary tin quartiles with total testosterone (T), and tin, nickel, zinc and molybdenum with the ratio of total T to luteinizing hormone (total T/LH ratio) (all P trend < 0.05). Additionally, we found significantly dose-dependent trends of increasing urinary manganese quartiles with increasing percentage of Annexin V +/PI − spermatozoa and increasing iron with decreasing percentage of PI + spermatozoa (both P trend < 0.05). These dose-dependent trends remained suggestive or significant after controlling for multiple testing and other metals, and they persisted when the metals were modeled as continuous variables in a cubic spline analysis. There were no significant associations between urinary metals and sperm DNA damage after adjustment for multiple testing. Conclusion: Environmental exposure to tin, nickel, zinc and molybdenum may be associated decreased total T or total T/LH ratio; manganese may induce spermatozoa apoptosis, while iron may be important for living spermatozoa. However, additional prospective research is needed to corroborate these findings in the general population. Highlights: We measured 18 heavy metals in repeated urine samples as exposure markers. Associations of the metals with hormones and sperm DNA integrity were assessed. Tin, nickel, zinc and molybdenum were inversely associated with T or T/LH ratio. Manganese was positively associated with percentage of Annexin V +/PI- spermatozoa. Urinary iron was inversely associated with percentage of PI + spermatozoa.